The Problem of the Formation of Sub-sectors of the Russian Criminal Law - Vasiliy Vasilevich Baburin (Сибирское юридическое обозрение, 2011)
This article explores contemporary issues of criminal law. Based on the analysis of the current situation in Russia and the international experience, a conditional selection in the Russian criminal law of several of its subsectors. Is offered are described by the base division on the proposed sub-sectors and measures to improve the existing system of criminal law.